2022
DOI: 10.2147/jpr.s360555
|View full text |Cite
|
Sign up to set email alerts
|

Fire Needling Acupuncture Suppresses Cartilage Damage by Mediating Macrophage Polarization in Mice with Knee Osteoarthritis

Abstract: Purpose Macrophage polarization contributes to the mechanisms of treating knee osteoarthritis (KOA). In previous studies, fire needling acupuncture has been shown to affect KOA favorably. However, the mechanism of fire needling acupuncture on macrophage polarization is not well-defined. Thus, this study was conducted to determine that fire needling acupuncture exerts a therapeutic role in KOA by modulating macrophage polarization. Methods Thirty mice were allocated at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Our research team has found that fire needling therapy decreases pain-related behaviors in KOA mice and improves synovial membrane injury and pathological cartilage damage. 43 However, fire needling therapy is rarely compared with the first-line drugs recommended by guidelines. 44 At the same time, the relationship between acupuncture dose and effect has been paid more attention by researchers, and it has been found that acupuncture frequency is one of the aspects of acupuncture dose, whereas the study about dose–effect property of fire needling therapy is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Our research team has found that fire needling therapy decreases pain-related behaviors in KOA mice and improves synovial membrane injury and pathological cartilage damage. 43 However, fire needling therapy is rarely compared with the first-line drugs recommended by guidelines. 44 At the same time, the relationship between acupuncture dose and effect has been paid more attention by researchers, and it has been found that acupuncture frequency is one of the aspects of acupuncture dose, whereas the study about dose–effect property of fire needling therapy is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Fire needle therapy has demonstrated efficacy in moderating and inhibiting cytokines such as IL-1, IL-6, IL-1β, and TNF-α, contributing to the reestablishment of immune balance. [30] (2) Mediation of inflammation:…”
Section: Fire Needle Mechanismmentioning
confidence: 99%
“…The fire needling applied to KOA mice confirmed this process. [32][33][34] Wang et al 35 found that after trinitrobenzene sulfonic acid (TNBS) stimulation, tyrosine hydroxylase immunoreactive (TH-IR) neurons in the L6 dorsal root ganglion of colitis rats increased and overgrew to sensory neurons, resulting in colitis and secondary hindfoot hypersensitivity. Applications of EA at ST36 and ST37 can reduce colitis and allergic reaction, which may be mediated by inhibiting TH-IR germination in L6 Dorsal root ganglion (DRG).…”
Section: Immune Cells and Neuronsmentioning
confidence: 99%